Strategi Komunikasi Pariwisata Pada Objek Wisata Puncak Pato Dalam Meningkatkan Kunjungan Wisatawan - Ainul Mardia; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Puncak Pato is one of the historical attractions located in Nagari Batu Bulek, North Lintau Buo District, Tanah Datar Regency, West Sumatra, Indonesia. Puncak Pato tourist attraction is one of the proofs of the birth of the Sati Bukik Marapalam Oath. The purpose of this study was to determine how the destination branding stages carried out by the manager or pokdarwis in introducing Puncak Pato tourist attraction. The method used is a qualitative research method with descriptive data type. The data collection techniques used are observation, interviews, and documentation. The results of the study use the concept of destination branding by Morgan and Pritchard, namely Market investigation, analysis, and strategic recommendations, managers strive to further improve and develop facilities for the sustainability of their tours, in the aspect of brand identity the manager still uses the motto Adat Basandi Syarak, Syarak Basandi Kitabullah as the identity of Puncak Pato tourism in the pledge of Sati Bukik Marapalam Oath. Meanwhile, in the brand launch aspect, the manager uses social media to promote tourism and the brand implementation aspect, the manager tries to make events every year and provide the best service to tourists. The last aspect is monitoring, evaluation and review by looking at the shortcomings that still exist such as the lack of tourists knowing about existing tour packages and will be strived for.